Comparison of Financial Performance of Private Commercial Banks in Pakistan - Baqir, Muhammad; Hussain, Sajid; Islam, K. M. Anwarul; Waseem, Rashid (American Finance & Banking Review, 2020)
Commercial banks play an important role for the purpose of sustainable economic development in a country. This paper main theme to presents the comparison of financial performance between private commercial banks in Pakistan during the period of 2015–2019 by using the method of ratio analysis and some other financial indicators. Fourteen Commercial banks out of fifteen banks are selected for comparison of financial analysis. Due to the unavailability of data, the remaining one bank is not chosen for study because, yet they did not publish their final report in 2019. The data of ratio analysis was captured by using the final report of commercial banks, which are available on the bank’s official websites. This study provides information about the different ratios which directly impact on bank performance.